Health Communication: Issues and Challenges (International Journal of Food and Nutritional Sciences, 2022)
Health communication, in the contemporary times, has assumed great significance than ever before. It is not only undergoing fast developments but integrates both interdisciplinary and multidisciplinary efforts to widen its nature and scope, applicability and dynamic nature. Its purpose is to promote wellness and healthy behaviours among masses in general. Believed to be one of the fastest growing areas of communication, health communication needs to strengthen its efforts and approaches to devise and improve its desired outcomes. The huge technological advancements can play an effective and engaging role in devising health communication strategies, health advocacy campaigns, health literacy and education programmes and other related content for all so that the objectives of achieving ‘sound health for all’ does not remain elusive. Focused and sustained efforts and campaigns are required to make health communication messages comprehensible and result-oriented using different communication channels and diverse media platforms.